Effect of NaOH Concentration on the Corrosion Behavior of 16Mn Steel in the Process of Producing Alumina - ZHOU Yuan, ZHOU Bin, ZOU Yong - qiang, PAN Xiao - hui, QUAN Bian - li (Cailiao Baohu, 2021)
In the process of alumina production from bauxite with high sulfur content by Bayer process, some factors such as NaOH concentration, S2- concentration and corrosion time have certain effects on the corrosion of equipment steel. The corrosion behavior of 16Mn steel under different NaOH concentrations was studied by electrochemical and weightless corrosion methods. The SEM was used to analyze the microscopic appearance of the corrosion products, the change rule of the composition of the corrosion products was analyzed according to the distribution of elements. Results showed that the corrosion rate of 16Mn steel increased with the increase of NaOH concentration, and decreased after reaching the maximum value. When the NaOH concentration was equal to 245 g/L, the corrosion rate was the maximum. The impedance arc radius began to decrease with the increase of NaOH concentration from 235 g/L to 245 g/L. The corrosion was mainly controlled by charge transfer, and the adsorption of S2- mainly occurred. When the NaOH concentration was equal to 255 g/L, the impedance spectrum showed a typical Warburg diffusion phenomenon. The corrosion process was mainly controlled by both ion diffusion and charge transfer, and the adsorption of OH- mainly occurred.